2018
DOI: 10.1016/j.nuclphysb.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter assisted Dirac leptogenesis and neutrino mass

Abstract: We propose an extension of the standard model with U (1)B−L × Z2 symmetry. In this model by assuming that the neutrinos are Dirac (i.e. B − L is an exact symmetry), we found a simultaneous solution for non zero neutrino masses and dark matter content of the universe. The observed baryon asymmetry of the universe is also explained using Dirac Leptogenesis, which is assisted by a dark sector, gauged under a U (1)D symmetry. The latter symmetry of the dark sector is broken at a TeV scale and thereby giving mass t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Such feeble couplings, in spite of their nonaesthetic nature, are generically present, if the sub-eV Dirac neutrino masses are generated by the Higgs-like mechanism with a vacuum expectation value (VEV) chosen around the electroweak scale. On the other hand, such a mechanism of neutrino mass generation is often criticized on account of naturalness, and dynamical explanations of the smallness of neutrino masses are, therefore, more biased by enlarging the Yukawa space and/or introducing sufficiently heavy particles, which have also been considered in explicit realizations of the DN [5][6][7][8][9].…”
Section: Dirac Neutrinogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Such feeble couplings, in spite of their nonaesthetic nature, are generically present, if the sub-eV Dirac neutrino masses are generated by the Higgs-like mechanism with a vacuum expectation value (VEV) chosen around the electroweak scale. On the other hand, such a mechanism of neutrino mass generation is often criticized on account of naturalness, and dynamical explanations of the smallness of neutrino masses are, therefore, more biased by enlarging the Yukawa space and/or introducing sufficiently heavy particles, which have also been considered in explicit realizations of the DN [5][6][7][8][9].…”
Section: Dirac Neutrinogenesismentioning
confidence: 99%
“…As an alternative to most DN applications in which the lepton-number asymmetry is generated by non-thermal heavy particle decays [3,[5][6][7][8][9], we have considered the case where the asymmetry is accumulated via the freeze-in production of right-handed neutrinos from thermal scalar decay.…”
Section: Thermal Scalar Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of X-particles and their interactions the mass matrix of X can be replaced with new mass matrix and after diagonalising the new mass matrix we get new mass eigenstates ξ ± 1 and ξ ± 2 . For further details [6]. The CP-violation arises via the interference of tree level and one loop self energy correction diagrams and the asymmetry ε L in the visible sector can be calculated.…”
Section: Lepton Asymmetry and Dark Matter Abundance From X-decaymentioning
confidence: 99%
“…[38] (subsequently in Ref. [39]) demonstrated that the inclusion of a small Majorana mass term for the singlet fermion in the Lagrangian splits the DM eigenstate into two nearly degenerate Majorana states with a tiny mass difference. In the small Majorana mass limit, the splitting does not make any difference to the relic abundance analysis; however, it makes a vital portal to the direct detection of the pseudo-Dirac DM candidate [38].…”
Section: Introductionmentioning
confidence: 97%